Unintentional Reverse Transfer from L2 (English) to L1 (Spanish) in Tertiary Levels - Luque Agulló, Gloria (International Journal of English Studies, 2020)
This study attempts to reveal whether there is unintentional reverse transfer L2→L1 (English-Spanish) in the oral L1 production of university learners in formal contexts. The languages used by learners influence each other, and this transfer may occur from the first to the second language (direct transfer), or from the second to the first (reverse transfer), the focus of this work. Thus, an exploratory study was implemented with two groups of participants with different L2 proficiency levels. They had to retell, using their L1, a soundless video. Their production was recorded, transcribed and examined. Consistent with other studies, results suggest unintentional reverse transfer occurs more frequently when there is a lower level of L2 competence, or, alternatively, its effects have a more evident negative outcome for these learners. Pedagogically speaking, being able to identify successful reverse transfer strategies with a positive outcome may have important implications for bilingual educational contexts.